The small ruminant and camel group and research network of the International Livestock Center for Africa of the International Livestock Center for Africa - Wilson, R.T. (Technical Centre for Agricultural and Rural Cooperation, 1988)
Overview of ILCA's "Small Ruminant of Camel Group" research network objectives and research priorites as well as future research plans to improve camels and small ruminant productivity in light of the existing production systems